A self‐applied valid scale for rapid tracking of household food insecurity among pregnant women in Sri Lanka - Thilini C. Agampodi; Amber Hromi‐Fiedler; Suneth B. Agampodi; Gayani S. Amarasinghe; Nuwan D. Wickramasinghe; Imasha U. Jayasinghe; Ayesh U. Hettiarachchi; Rafael Perez‐Escamilla (Wiley, 2021)
Abstract Rapid household food insecurity (HFI) tracking has been identified as a priority in the context of the COVID‐19 pandemic and its aftermath. We report the validation of the Latin American and Caribbean Food Security Scale (Escala Latinoamericana y Caribena de Seguridad Alimentaria [ELCSA]) among pregnant women in Sri Lanka. The eight‐item adult version of the ELCSA was translated from English to Sinhala and Tamil. Cognitive testing (on 10 pregnant women and five local experts) and psychometric validation of the self‐administered HFI tool were conducted among pregnant women (n = 269) attending the special clinics of the Rajarata Pregnancy Cohort (RaPCo) in Anuradhapura in February 2020. We assessed the psychometric properties and fit using a one parameter logistic model (Rasch model analysis) using STATA Version 14 and WINSTEP software Version 4.3.4. Concurrent validity was tested using psychological distress. The scale was internally consistent (Cronbach's alpha = 0.79) and had a good model fit (Rasch items infit statistic range: 0.85 to 1.07). Item 8 ('did not eat for the whole day') was removed from the model fit analysis, as it was not affirmed by respondent. Item severity scores ranged from −2.15 for 'not eating a diverse diet' to 4.43 for 'not eating during the whole day'. Concurrent validity between HFI and psychological distress was confirmed (r = 0.15, p < 0.05). The self‐applied version of ELCSA‐pregnancy in Sri Lanka (ELCSA‐P‐SL) is a valid and feasible valid tool. We recommend it to track HFI among pregnant women in lower income countries during the COVID‐19 pandemic.